Magnetically Actuated Degradable Microrobots for Actively Controlled Drug Release and Hyperthermia Therapy. Issue 16 (10th July 2019) - Park, Jongeon; Jin, Chaewon; Lee, Seungmin; Kim, Jin‐Young; Choi, Hongsoo
Abstract: Microrobots facilitate targeted therapy due to their small size, minimal invasiveness, and precise wireless control. A degradable hyperthermia microrobot (DHM) with a 3D helical structure is developed, enabling actively controlled drug delivery, release, and hyperthermia therapy. The microrobot is made of poly(ethylene glycol) diacrylate (PEGDA) and pentaerythritol triacrylate (PETA) and contains magnetic Fe3 O4 nanoparticles (MNPs) and 5‐fluorouracil (5‐FU). Its locomotion is remotely and precisely controlled by a rotating magnetic field (RMF) generated by an electromagnetic actuation system. Drug‐free DHMs reduce the viability of cancer cells by elevating the temperature under an alternating magnetic field (AMF), a hyperthermic effect. 5‐FU is released from the proposed DHMs in normal‐, high‐burst‐, and constant‐release modes, controlled by the AMF. Finally, actively controlled drug release from the DHMs in normal‐ and high‐burst‐release mode results in a reduction in cell viability. The reduction in cell viability is of greater magnitude in high‐burst‐ than in normal‐release mode. In summary, biodegradable DHMs have potential for actively controlled drug release and hyperthermia therapy. Abstract : A degradable hyperthermia microrobot (DHM), which encapsulates 5‐fluorouracil and Fe3 O4 nanoparticles is developed and demonstrates the potential for actively controlled drug release and hyperthermia therapy. The locomotion of the DHM is remotely controlled by a rotating magnetic field. The alternating magnetic field not only increases the temperature of the DHMs, but also actively controls the drug release from the DHMs.